The exp-function method for new exact solutions of the nonlinear partial differential equations - Naher, Hasibun; Abdullah, Farah Aini; Akbar, M. Ali (© 2011 International Journal of Physical Sciences, 2016)
This article was published in the International Journal of Physical Sciences [© 2011 Academic Journals] and the definite version is available at : 10.5897/IJPS11.1026